Espiritismo, saúde e caridade: um estudo biográfico sobre a família Silva e Souza, em Santa Maria/RS - Girardi, Felipe (2017)
This dissertation approaches the trajectory of Silva and Souza Family, in Santa Maria (RS) through the couple João da Fontoura e Souza and Florina da Silva e Souza, highline leadership of spiritual movement of Santa Maria/RS, and their children. In this work, it is stand out especially the linking of family with many spiritual institutions in the town and with the practice of homeopathy, from the foundation of Farmácia Homeopática Cruz Vermelha, in 1926. The elements, and others, as the practice of charity by work of assistance, will be analyzed in the sense to comprehend the establish relation among them by the family. I should emphasize that this work aim to elaborate a biographical speech about Silva e Souza family, situated in the historical context of santa-mariense spirit movement. In this meaning, the focus of reflection is directed to the constitution of familiar memory, from the elaborated report by the relatives in texts of biographical and autobiographical character, beyond of other documental sources produced by people and by institutions in which they were connected.